Mild Methylenetetrahydrofolate Reductase Deficiency Alters Inflammatory and Lipid Pathways in Liver. Issue 3 (23rd November 2018) - Leclerc, Daniel; Christensen, Karen E.; Cauvi, Olivia; Yang, Ethan; Fournelle, Frédéric; Bahous, Renata H.; Malysheva, Olga V.; Deng, Liyuan; Wu, Qing; Zhou, Zili; Gao, Zu‐Hua; Chaurand, Pierre; et al.
Abstract : Scope: Dietary and genetic folate disturbances can lead to nonalcoholic fatty liver disease (NAFLD). A common variant in methylenetetrahydrofolate reductase ( MTHFR 677C→T) causes mild MTHFR deficiency with lower 5‐methyltetrahydrofolate for methylation reactions. The goal is to determine whether mild murine MTHFR deficiency contributes to NAFLD‐related effects. Methods and results: Wild‐type and Mthfr +/− mice, a model for the human variant, are fed control (CD) or high‐fat (HFAT) diets for 8 weeks. On both diets, MTHFR deficiency results in decreased S ‐adenosylmethionine, increased S ‐adenosylhomocysteine, and decreased betaine with reduced methylation capacity, and changes in expression of several inflammatory or anti‐inflammatory mediators ( Saa1, Apoa1, and Pon1 ). On CD, MTHFR deficiency leads to microvesicular steatosis with expression changes in lipid regulators Xbp1s and Cyp7a1 . The combination of MTHFR deficiency and HFAT exacerbates changes in inflammatory mediators and introduces additional effects on inflammation ( Saa2 ) and lipid metabolism ( Nr1h4, Srebf1c, Ppara, and Crot ). These effects are consistent with increased expression of pro‐inflammatory HDL precursors and greater lipid accumulation. MTHFR deficiency may enhance liver injury through alterations in methylation capacity, inflammatory response, and lipid metabolism. Conclusion: Individuals with the MTHFR variant may be at increased risk for liver disease and related complications, particularly when consuming high‐fat diets. Abstract : Mild 5, 10‐methylenetetrahydrofolate reductase (MTHFR) deficiency in mice may exacerbate nonalcoholic fatty liver disease (NAFLD) complications through reduced methylation capacity, disturbances in choline/betaine metabolism, and altered expression of genes in lipid metabolism or inflammation (APR genes or genes encoding anti‐ and pro‐inflammatory proteins of precursor HDL). The Mthfr +/− mouse is a good model for the human MTHFR 677C→T polymorphism. Therefore, individuals with this polymorphism may be at increased risk for liver disease and related complications.